SiC MOSFET Based 10 kW Interleaved Boost Converter Interface for Regenerative Power Electronic System - R. G. Arrshith; M. R. Rashmi; Vigna K. Ramachandaramurthy; Hoong Pin Lee; Umashankar Subramaniam (IEEE Access)
DC-dc converters are used widely in applications such as industrial, renewable energy, and electric vehicles, etc. In the present scenario, there is a need for high-power and compact dc-dc converters, which can be achieved by interleaving multiple power stages of a particular topology. In industries, a step-up dc-dc converter interface is required to test and validate various industrial power supplies with different voltage ratings. The step-up dc-dc converter will serve as a universal step-up interface between an industrial power supply, which is referred to as Device Under Test (DUT), and a bidirectional power supply to recirculate the power drawn to the grid, saving a great amount of power. In this work, a high-power, three-phase/stage step-up interleaved dc-dc converter of 10 kW is developed and experimentally validated for input voltages ranging between 120 V and 200 V for the fixed output voltage of 450 V. The maximum power that can be obtained is 32 kW. The setup is tested for 10 kW power. The converter is developed using Silicon Carbide MOSFET devices. SiC devices help in energy conservation. A double pulse test is performed to compare switching losses between a second-generation Silicon Carbide (SiC) MOSFET and a fifth-generation Silicon IGBT. The performance of the SiC MOSFET is found to be better. Therefore, SiC MOSFETs are used. The advantage of inherent phase current balancing is achieved by using Peak Current Mode Control (PCMC), and the proposed control strategy can be applied for any number of phases. Three-phase boost converters have been chosen because it is practically feasible to achieve higher power density compared to a single-stage boost converter. Thermal imaging of the converter is obtained, and the measured temperature rise in the MOSFETs was found to be 51.40°C, which is less than the maximum allowed temperature of 100°C. The results are compared with the existing topologies. In the literature, the topologies are developed for low power ratings, and the component count is also higher. In this work, an efficient, high-power, interleaved dc-dc converter is developed with a less number of components.